2017
DOI: 10.1111/cdev.12866
|View full text |Cite
|
Sign up to set email alerts
|

Empowering Marginalized Youth: A Self‐Transformative Intervention for Promoting Positive Youth Development

Abstract: This article reports the results of a positive youth development (PYD) intervention for adolescents in alternative high schools (209 African American and Hispanic American adolescents, aged 14-18; 118 females and 91 males). The intervention was guided by a self-transformative model of PYD (Eichas, Meca, Montgomery, & Kurtines, 2014). This model proposes that the actions youth take to define themselves function as active ingredients in positive development over the life course. Consistent with the self-transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 30 publications
2
20
0
6
Order By: Relevance
“…A different PYD intervention—the Changing Lives Program—was examined among a sample of Latino and African American adolescents. Results validate the success of positive interventions for reducing problems (Eichas, Montgomery, Meca, & Kurtines, ).…”
supporting
confidence: 58%
“…A different PYD intervention—the Changing Lives Program—was examined among a sample of Latino and African American adolescents. Results validate the success of positive interventions for reducing problems (Eichas, Montgomery, Meca, & Kurtines, ).…”
supporting
confidence: 58%
“…Taken globally, these finding are consistent with the success markers associated with positive youth development. For example, research in this area has referenced the impact of meaningful opportunity interventions and the empowerment of youth to be accountable for their own development (Eichas et al, 2017). Eichas et al found positive youth development interventions to have cascades and "spill over" effects on several different but related inter and intrapersonal qualities in youth.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of social identities is very visible in this special section and explicitly addressed in the study by Eichas, Montgomery, Meca, and Kurtines () where marginalized adolescents' self‐transformation—focused on a model of youth agency, aspiration, and advancement—is studied in an alternative school context. However, several studies in the special section consider identity as it is embedded in diverse contexts globally, from immigrant youth in Greece (Motti‐Stefani, ) to migrant youth in KwaZulu‐Natal (Schwartz, Theron, & Scales, ) and among youth and families in Turkey (Laible, Kumru, Gustavo, Streit, Yagmurlu, & Sayil, 2017).…”
Section: Overview Of the Special Sectionmentioning
confidence: 98%